Penggunaan Aplikasi Canva Dalam Meningkatkan Efektivitas Pembelajaran PAI Di SMP Negeri 2 Kendit Situbondo - Maula, Rohmatil; Fauzi, Ahmad; Sofa, Ainur Rofiq (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
The purpose of this study is to evaluate how well the Canva app enhances Islamic Religious Education (PAI) instruction at SMP Negeri 2 Kendit Situbondo. research methodology is used, and data gathering methods include observation, interviews, and documentation. Canva is utilized as a learning medium to present materials in the form of infographics, presentations, and engaging, interactive educational videos. The results indicate that the use of Canva can increase students' learning interest, clarify their understanding of Islamic concepts, and encourage active participation in the learning process. Teachers also become more creative in delivering materials, making the classroom atmosphere more dynamic and effective. Additionally, the use of Canva helps develop students' and teachers' digital skills in utilizing educational technology. This visual-based learning approach not only makes students more enthusiastic but also facilitates their ability to remember and apply religious values in daily life. Thus, integrating the Canva application into PAI learning serves as an innovative solution to enhance learning effectiveness in the digital era, providing students with a more engaging, enjoyable, and meaningful learning experience.